(untitled) (Edad Media. Revista de Historia, 2023)
This article analyzes the geographical mobility towards the city of Valencia between 1416 and 1470, mainly based on the labour, marriage and slave markets, although the proportion of individuals who dictated their last wishes far from their hometowns has also been estimated. In particular, we have analyzed certain documentation preserved in the 37 notarial protocols of Jaume Vinader, dated between 1416 and 1470, from both a quantitative and qualitative point of view. Thus we have been able to observe a flow of people during childhood, the age of marriage and, to a lesser extent, between nuptials and the moment of dictating the last will and testament.